Dinamika Politik Hukum dalam Penyelesaian Konflik melalui Jalur Mediasi di Indonesia - Ismaidar Ismaidar; Tamaulina Br. Sembiring; Bonari Tua Silalahi (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
The dynamics of legal politics in resolving conflicts through mediation in Indonesia. The mediation process is an alternative dispute resolution that is increasingly popular in Indonesia, both in the context of civil and socio-political conflicts. This research aims to analyze the role of mediation in resolving conflicts as well as the impact of legal politics involved in this process. Mediation in Indonesia often involves political factors that influence the course of the process, both from the government, judicial institutions and other related parties. In this study, the author examines various cases of successful and failed mediation, and explores how political intervention can strengthen or hinder the effectiveness of mediation. The research results show that although mediation offers a peaceful solution, political dynamics are often an obstacle that needs to be considered in optimizing this route as a means of resolving disputes. This paper is expected to provide a deeper understanding of the challenges and opportunities of mediation in the Indonesian legal system.